2019
DOI: 10.1111/rssa.12463
|View full text |Cite
|
Sign up to set email alerts
|

What did you Really Earn Last Year?: Explaining Measurement Error in Survey Income Data

Abstract: Summary The paper analyses the sources of income measurement error in surveys with a unique data set. We use the Austrian 2008–2011 waves of the European Union ‘Statistics on income and living conditions' survey which provide individual information on wages, pensions and unemployment benefits from survey interviews and officially linked administrative records. Thus, we do not have to fall back on complex two‐sample matching procedures like related studies. We empirically investigate four sources of measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Finally, a relative importance analysis highlights the magnitude of each explanatory variable's contribution to the overall reporting bias. The empirical strategy employed is based on a recent study by Angel et al [41], who analysed the reporting bias in survey-based income data. All of our analyses are first applied to indicators of mobility and then to indicators of cognition.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a relative importance analysis highlights the magnitude of each explanatory variable's contribution to the overall reporting bias. The empirical strategy employed is based on a recent study by Angel et al [41], who analysed the reporting bias in survey-based income data. All of our analyses are first applied to indicators of mobility and then to indicators of cognition.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review on the determinants of social desirability bias in surveys found income to be a particularly sensitive survey topic due to the social context of the question [26]. Two recent studies comparing differences in self-reported and actual income found strong evidence for social desirability bias in self-reported income, resulting in inflated values [27,28]. We were told by MSU Extension agents that farmers and ranchers were unlikely to provide accurate responses to questions about financial health.…”
Section: Joint Health and Economic Health In Agriculturementioning
confidence: 99%
“…(21) Two recent studies comparing differences in self-reported and actual income found strong evidence for social desirability bias in self-reported income, resulting in inflated values. (22,23) We were told by MSU Extension agents that farmers and ranchers were unlikely to provide accurate responses to questions about financial health. Therefore, we relied more on the surrogate indicators of reduced work capacity and the need to rely on others to perform work.…”
Section: Discussion Joint Health and Economic Health In Agriculturementioning
confidence: 99%